The great dinosaur search - Heywood, Rosie; Wingate, Philippa; Inklink (Firm); Studio Galante (London : Usborne, 2005)
Presents color illustrations that contain hidden pictures of dinosaurs and other plants and animals that lived with them in different prehistoric eras; and includes facts and descriptions of the various creatures.
At head of title: Usborne.
Includes index.
4.4
K-3
Keywords: Dinosaurs; Puzzles